1999
DOI: 10.1002/(sici)1096-8628(19990820)88:4<430::aid-ajmg23>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

No association between serotonin transporter gene polymorphisms and personality traits

Abstract: Human family and twin studies have established considerable heritable components in personality traits as assessed by self-report questionnaires. Recently, an association between a functional polymorphism in the upstream regulatory region of the serotonin transporter gene and neuroticism-related personality traits was reported. Two different serotonin transporter polymorphisms including the previously associated variant were genotyped in two samples of healthy Swedish subjects (n = 127 and n = 178, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 53 publications
0
35
0
1
Order By: Relevance
“…This was between avoidance traits and the 5HTT LPR polymorphism (P ¼ 0.038). A crude estimate of the effect size of 26 Control participants not scored for personality Benjamin et al 34 Data reported elsewhere Benjamin et al 43 Subscale data reported only Blairy et al 45 Too few papers reporting data on this gene to analyse Comings et al 36 Data reported elsewhere Comings et al 19 Subscale data reported only Comings et al 47 Too few papers reporting data on this gene to analyse Damberg et al 48 Subscale data reported only Deary et al 27 Extreme scores design Duaux et al 32 Data not released Ekelund et al 28 Extreme scores design Gustavsson et al 57 Subscale data reported only Jang et al 40 Data reported elsewhere Jonsson et al 63 Subscale data reported only Jonsson et al 62 Subscale data reported only Jonsson et al 61 Subscale data reported only Jonsson et al 29 Subscale data reported only Jorm et al 65 Too few papers reporting data on this gene to analyse Lerman et al 31 Data not released Manuck et al 73 Too few papers reporting data on this gene to analyse Manuck et al 72 Too few papers reporting data on this gene to analyse Mel et al 35 Data reported elsewhere Melke et al 74 Subscale data reported only Nielsen et al 77 Subscale data reported only Persson et al 30 Subscale data reported only Persson et al 81 Too few papers reporting data on this gene to analyse Ricketts et al 83 Data reported elsewhere Sher et al 38 Data reported elsewhere Sirota et al 37 Data reported elsewhere Strobel et al 24 Data reported elsewhere Tsai et al 89 Too few papers reporting data on this gene to analyse Vandenbergh et al 90 Extreme scores design the 5HTT LPR polymorphism on avoidance traits suggested that the genotypic effect accounted for less than 10% of the phenotypic variance, but this figure should ...…”
Section: Discussionmentioning
confidence: 99%
“…This was between avoidance traits and the 5HTT LPR polymorphism (P ¼ 0.038). A crude estimate of the effect size of 26 Control participants not scored for personality Benjamin et al 34 Data reported elsewhere Benjamin et al 43 Subscale data reported only Blairy et al 45 Too few papers reporting data on this gene to analyse Comings et al 36 Data reported elsewhere Comings et al 19 Subscale data reported only Comings et al 47 Too few papers reporting data on this gene to analyse Damberg et al 48 Subscale data reported only Deary et al 27 Extreme scores design Duaux et al 32 Data not released Ekelund et al 28 Extreme scores design Gustavsson et al 57 Subscale data reported only Jang et al 40 Data reported elsewhere Jonsson et al 63 Subscale data reported only Jonsson et al 62 Subscale data reported only Jonsson et al 61 Subscale data reported only Jonsson et al 29 Subscale data reported only Jorm et al 65 Too few papers reporting data on this gene to analyse Lerman et al 31 Data not released Manuck et al 73 Too few papers reporting data on this gene to analyse Manuck et al 72 Too few papers reporting data on this gene to analyse Mel et al 35 Data reported elsewhere Melke et al 74 Subscale data reported only Nielsen et al 77 Subscale data reported only Persson et al 30 Subscale data reported only Persson et al 81 Too few papers reporting data on this gene to analyse Ricketts et al 83 Data reported elsewhere Sher et al 38 Data reported elsewhere Sirota et al 37 Data reported elsewhere Strobel et al 24 Data reported elsewhere Tsai et al 89 Too few papers reporting data on this gene to analyse Vandenbergh et al 90 Extreme scores design the 5HTT LPR polymorphism on avoidance traits suggested that the genotypic effect accounted for less than 10% of the phenotypic variance, but this figure should ...…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the original finding of higher neuroticism and harm avoidance in adult individuals with the short variant of the 5HTTLPR has been replicated and extended to younger individuals 3 and to other anxietyrelated dimensions of personality, [4][5][6] but has also failed replication. [7][8][9][10][11][12][13] Similarly, studies examining possible association between allelic variation in the promoter region of the serotonin transporter gene and risk for unipolar and bipolar depression have produced inconsistent findings (reviewed in Furlong et al 14 ). Among the potential sources for differences among these findings is the possibility that environmental variables may play an important role in the functional expression of the genotype.…”
mentioning
confidence: 99%
“…Unfortunately, most subsequent studies have failed to replicate the original findings. [8][9][10][11][12][13][14][15][16][17][18][19] There have also been a number of studies examining associations with anxiety and affective disorders. Most of these studies have also been negative, [20][21][22][23][24][25][26][27] although one study found that the long allele was associated with obsessive-compulsive disorder.…”
mentioning
confidence: 99%